PERAN GURU BK MASA KINI: SEBUAH KAJIAN TENTANG FENOMENA PENDIDIKAN INDONESIA - Ali Daud Hasibuan (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
21st century human resources have three pillars, namely literacy, competence, and character. Literacy is the ability to read, reading interest, and reading power of every writing and environmental phenomenon to be used as life learning. Competence is a skill in critical thinking, creating creativity, collaborating, and communicating good and true. Character is the attitudes and plates possessed in accepting and carrying out the tasks carried. The three pillars can be realized through the correct learning process. Cooperation of school institutions, community, and student families can be done with the method of exemplifying each other, collaborate in kretaivitas, and mutually motivate in achievement. Teacher BK acts as an educator who can help students to be physically and psychologically ready to follow, understand, accept, and mangamalkan learning process as well as possible. BK Teachers can conduct activities that are understand, control, alleviate, maintain, and develop the potential of the students.Keywords: Teachers BK, potential students, learning process